Perspektif Guru Mengenai Penerapan Media Pembelajaran Interaktif Berbantuan Power Point Pada Anak Usia 5-6 Tahun di TK Negeri Pembina Kota Semarang - Tasya Auprilia Putri; Reni Pawestuti Ambari Sumanto (Universitas Pendidikan Ganesha, 2023)
As the first institution for early childhood, PAUD institutions must have a directed learning system to achieve optimal growth and development of children so that children are ready to face the next level of education. This research aims to explain the teacher's perspective regarding the application and use of interactive learning-based media with the help of PowerPoint as an alternative in the learning process for children aged 5-6 years. This research uses a descriptive qualitative method with a phenomenological design. Data was collected through observation and interviews with 7 teachers at the kindergarten. The data analysis technique in this research uses data collection analysis, data reduction, data presentation, and verification. The analysis results show that using interactive learning media provides benefits in increasing students' interest and ease in studying learning material. Teachers see that interactive learning media has helped them convey learning objectives and attract children's attention. Even though there are several obstacles to implementing interactive learning media, teachers think the media is worth using. This research provides a better understanding of teachers' perspectives on applying interactive learning media. It provides a basis for further development in using these media as practical learning tools.